Education on sharia drug use in bipolar disorder patients during fasting month at Prof. dr. Soerojo Mental Hospital Magelang - Arifin Santoso; Ishak; Nadila Prameswari (Universitas Muhammadiyah Malang, 2023)
Bipolar disorder is an emotional state or mood that ranges from manic (high) to depressive. The role of the Qur'an in dealing with mental disorders can be as a therapist in changing the mind, personality of the patient gradually, and as a healer for patients suffering from mental disorders. The purpose of this study was to determine the impact of sharia drug use education on bipolar patients at Prof. Dr. Soerojo Magelang Mental Hospital during the fasting month. Methods: This research is a descriptive qualitative research. Data collection for this study was conducted in February-March 2023. This study used a questionnaire as a tool to collect data and information media delivered through brochures. The results showed that bipolar disorder cases mostly had female gender characteristics (52%), and most had high school education (80%) as the last recorded education. With the results of the percentage value of understanding sharia drug use education in bipolar disorder patients, there is an increase in the influence on the success of patient therapy in peace of mind, quality of life and compliance in taking medication.